Pengaruh Implementasi Manajemen Kelas Berbasis Flipped Classroom Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Matematika Siswa Kelas XI di SMAN 4 Denpasar - Pratiwi, Gusti Ayu Nyoman Ratih Arik; Widiana, I Wayan; Werang, Basilius Redan (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to find out: (1) whether the critical thinking skills of students who follow flipped classroom-based classroom management are better than students who follow conventional classroom management, (2) whether the learning outcomes of students who follow flipped classroom-based classroom management are better than students who follow conventional classroom management, (3) whether critical thinking skills and learning outcomes simultaneously between students who Following Flipped Classroom-based classroom management is better than students following conventional classroom management. This research is a pseudo-experimental research with a post-test only control group design. The data were analyzed using the Manova test with a significance level of 5%. The experimental results showed that: (1) the critical thinking skills of students who followed flipped classroom-based classroom management were better than students who followed conventional classroom management, (2) the learning outcomes of students who followed flipped classroom-based classroom management were better than students who followed conventional classroom management, (3) critical thinking skills and learning outcomes simultaneously between students who followed classroom management Flipped classroom-based is better than students who follow conventional classroom management. This is because students who take part in flipped classroom-based classroom management are more enthusiastic about following the learning process in class because they have previously studied the material in their respective home learning videos. Students are also trained to re-express their understanding with group discussions.